Teacher reform in Indonesia : the role of politics and evidence in policy making - Chu-Chang, Mae, 1953-; Shaeffer, Sheldon; Al-Samarrai, Samer; Ragatz, Andrew B.; De Ree, Joppe, 1975-; Stevenson, Ritchie (Directions in development (Washington, D.C.). Human development., 2014)
The book features an analysis of teacher reform in Indonesia, which entailed a doubling of teacher salaries upon certification. It provides a description of the political economy context in which the reform was developed and implemented and an analysis of the impact of the reform on teacher knowledge, skills, and student outcomes. It includes a randomized control trial over time with data representative of approximately 50 percent of the country's primary and junior secondary schools and a time-on-task analysis of a representative sample of classroom teaching practices linked to the TIMSS ...